Effect of Service Quality on Customer Satisfaction PT. Pos Indonesia (Persero) Kupang Branch - Setyorini, Tuti; Yolandari, Marni (CV. Jala Berkat Abadi, 2023)
This study aims to aim to determine the influence of service quality factors on customer satisfaction at PT. Pos Indonesia (Persero) Kupang Branch either partially or simultaneously. The number of samples taken in this study amounted to 50 respondents. The method used to test the hypothesis is to perform the t-test and F-test procedures. Based on the data from the research results, it can be concluded that the service quality factors that have a significant effect on customer satisfaction partially are reliability and empathy. While simultaneously, service quality has a significant effect on customer satisfaction